Uslūb Al- Jinās dalam Puisi Qalbiy ‘alaika Habībatiy Karya Aiman al-Otoom - Nurul Aini Pakaya (Universitas Muhammadiyah Gorontalo, 2022)
Arabic is known as a language that has a unique and beautiful style of language, the beauty of the language is also reflected in the combination of the beauty of meaning and pronunciation. One of the studies in balagah science is badi' science which specifically examines the beauty of lafadz and meaning, and one of the studies in badi' science is jina>s. in badi' science, jina>s are categorized as al-Muhassina>t al-Lafdziyyah. The purpose of the research in this article is to find out the elements of jina>s in Aiman al-Otoom's poetry. The research method is descriptive analysis with the type of library research, and the source of the research data is Aiman al-Otoom's poem entitled Qalbiy 'alaika Habībatiy and books and scientific articles related to the study of balagah. The results showed that in li'ainaika poetry, jinas were only found in 11 stanzas consisting of 8 stanzas of Jina>s Ta>m, and 3 stanzas of Jina>s Gairu Ta>m. And the lasta tuba>liy poem consists entirely of 21 stanzas, and 6 stanzas of which there are jinas, 4 stanzas of Jina>s Ta>m and 3 stanzas of Jina>s Gairu Ta>m.